PENGARUH IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) TERHADAP PRODUKTIVITAS DENGAN KEPEMIMPINAN SEBAGAI VARIABEL MODERATING PADA PT. PERKEBUNAN NUSANTARA V LUBUK DALAM KABUPATEN SIAK - Raja, Saikiamin Fenny; Iwan, Daulay Nauli; Rio, Marpaung JM (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of total implementation Quality Management (TQM) Towards Productivity With Leadership As a Moderating Variable in PT. Perkebunan Nusantara V Lubuk Dalam Siak Regency. The population in this study includes all section employees production at PT. Perkebunan Nusantara V Lubuk Dalam Siak Regency, which totaling 53 people. Primary data were collected by questionnaire as an instrument for prove the results of research, to test the hypothesis in this study is using multiple linear regression analysis with the help of the SPSS program. The sampling technique that has been selected is the census method (53 people PT. Perkebunan Nusantara V Lubuk Dalam Regency Siak). The results showed: 1) there was a positive influence and significant Total Quality Management of productivity in employees of PT. Perkebunan Nusantara V Lubuk In Siak Regency, 2) there is influence positively and significantly moderated total Quality Management Leadership on productivity of employees at PT. Plantation Nusantara V Lubuk Dalam Siak Regency.Keywords: Total Quality Management, Leadership, Productivity